Evidence-Based Strength Training: Best Practices for Enhancing Athletic Performance - Cao Yulin; Li Jingwen (Ilmu Inovasi Nusantara, 2025)
Physical training forms the foundation of sports training, with strength training being its most critical and essential component. Strength training enhances athletic performance by improving power, endurance, and physical capability. Despite its importance, the methods and parameters for optimizing strength training remain a subject of continuous study and debate among researchers and practitioners. This study addresses this gap by reviewing and analyzing current international research on the best practices for strength training. Specifically, it focuses on identifying the most effective forms of training, optimal intensities, volumes, and frequencies for achieving peak athletic performance. The methodology includes a comprehensive literature review of peer-reviewed journals, meta-analyses, and experimental studies on strength training. The research synthesizes findings to identify patterns and recommendations that can be tailored to the specific needs of Chinese athletes. The analysis reveals that strength training effectiveness depends on individual athlete characteristics, such as age, sport specialization, and training experience. Key findings suggest that high-intensity, low-volume training benefits explosive power sports, while moderate-intensity, high-volume regimens are better suited for endurance-focused disciplines. Training frequency, periodization, and recovery protocols also emerge as crucial factors influencing outcomes. Based on these findings, the study recommends that coaches and sports scientists in China adopt a personalized approach to designing strength training programs. This includes integrating evidence-based practices with Chinese athletes' unique physiological and cultural contexts to maximize training efficacy. Future research should explore long-term adaptations and sport-specific applications to refine these strategies further